Never grow up - Gurney, Stella; Al Blyth; Blake, Quentin (London puffin books, 2022)
"A brand new picture book inspired by Roald Dahl and illustrated by Quentin Blake It's rotten when you're very small, You hardly get a say at all. It's No! and Quiet! and That's enough! By golly, life - it can be tough . . . Inspired by the work of the world's number 1 storyteller, this picture book is a guide to growing up the Roald Dahl way, with gloriumptious illustrations by Quentin Blake. A celebration of all the tremendous things children have in store - from adventure to inventions, chocolate cakes to rhino poo - along with a reminder that the very best grown ups are those who hold on tight to the chiddler inside."--Provided by publisher
English stories
Inspired by the mischief and magic of Roald Dahl
Keywords: Children Juvenile fiction; Children's stories Pictorial works; English fictions